Use of an Under-Water Compressed Air Energy Storage (UWCAES) to Fully Power the Sicily Region (Italy) With Renewable Energy: A Case Study - Tiano, Francesco Antonio; Rizzo, Gianfranco (Frontiers in Mechanical Engineering, 2021)
The high concentration of CO2 in the atmosphere and the increase in sea and land temperatures make the use of renewable energy sources increasingly urgent. To overcome the problem of non-programmability of renewable sources, this study analyzes an energy storage system consisting of under water compressed air energy storage (UWCAES). A case study for fully power the Sicily region (Italy) with renewable energy source (wind and photovoltaic) is presented. From the real annual capacity values of the renewable plants installed in Sicily, a sizing of both the energy production and the storage system and its auxiliary services is evaluated. The optimization of the operation of the system as a whole, modeled with mathematical models already validated in previous studies, is obtained through dynamic programming. The electricity consumed annually by the region, equal to 19048.4 GWh, can be entirely satisfied by renewable energy sources. A sizing of plants powered by renewable sources for a nominal power of 15, 000 MW equally divided between photovoltaic and wind power is considered. The underwater air storage system has a maximum volume of 2.1 × 108 m3, while the compression and generation units have a total nominal power of 6, 900 and 3, 100 MW, respectively. The study finally presents a sensitivity analysis for the evaluation of the effects of the variation of the power produced by renewable energy sources and of Sicily energy consumption. The results show that carbon-free feeding is possible and that all the boundary conditions on the operation of the system can be met.